MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATA PELAJARAN SOSIOLOGI POKOK BAHASAN PERILAKU MENYIMPANG MELALUI STRATEGI PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS X5 SMA NEGERI 3 BANJARMASIN - Tri Guwati (JURNAL SOCIUS, 2012)
The purpose of this research is to describe the students' motivation and study result of X5 SMA Negeri 3 Banjarmasin to deviant behavior material which can be improved by using student teams achievement division (STAD) as teaching strategy.The Method which used on this classroom action research is qualitative analysis, which emphasizes on the research problem especially in improving the motivation and study result of students in sociology. Therefore, the problem can be identified and analyzed then found alternative solutions, there 35 students as samples on X5 class SMA Negeri 3 BanjarmasinThe results of the research shows that: (1) motivation to study sociology on X5 students of SMA Negeri 3 Banjarmasin while using STAD as teaching strategy is improved, (2) the study result of X5 students of SMA Negeri 3 Banjarmasin on sociology by using STAD as teaching strategy s increased, (3) the X5 students of SMA Negeri 3 Banjarmasin response on the use of teaching strategy like STAD shows that the students like and enjoy studying sociology by using STAD as a teaching strategy.Kata Kunci:  motivasi, hasil belajar, STAD, sosiologi